The Effect of Flexible Working Arrangements on Work Engagement of Online Motorcycle Taxi Drivers - Umi Farida (Psychological Research and Intervention, 2020)
This study aims to determine the effect of flexible working arrangements on the work engagement of online motorcycle taxi drivers. This research used a quantitative approach and included ex-post facto research. This study used 297 online motorcycle taxi drivers in the Special Region of Yogyakarta. The data collection technique used a measuring instrument in the form of a psychological scale that has been tested for validity and reliability. The psychological scale is the work engagement scale with Cronbach's Alpha 0.881 and the flexible working arrangements scale with Cronbach's Alpha 0.910. The data analysis technique to test the research hypothesis used a simple regression test. Based on the data analysis, the regression coefficient was 1.636 and sig. 0.0000.005 with R Square=0.671. These results indicate an effect of flexible working arrangements to work engagement positively and significantly by 67,1%.